1982
DOI: 10.1177/000992288202100203
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Group A Streptococcal Pharyngitis in Children

Abstract: Penicillin V, benzathine/procaine penicillin G, cefadroxil monohydrate, and erythromycin estolate were randomly assigned for therapy of group A streptococcal pharyngitis in 198 children. All patients improved with in 24 hours of initiating therapy. Reinfection with a new group A streptococcal serotype occurred in 13 patients, 12 developing 7 to 12 days after stopping therapy and 11 becoming symptomatic. Relapse with the same organism occurred in 16 patients, only 5 (31%) of whom were symptomatic. Antibody tite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Five studies reported intramuscular penicillin therapy; results were consistent with our findings for antibiotics overall [31,34,40,54,55]. Snellman et al found 1/15 (6.7%) children were culture-positive at 24 h following single dose benzathine penicillin [31].…”
Section: Culture Positivity During Antibiotic Treatmentsupporting
confidence: 87%
See 2 more Smart Citations
“…Five studies reported intramuscular penicillin therapy; results were consistent with our findings for antibiotics overall [31,34,40,54,55]. Snellman et al found 1/15 (6.7%) children were culture-positive at 24 h following single dose benzathine penicillin [31].…”
Section: Culture Positivity During Antibiotic Treatmentsupporting
confidence: 87%
“…Brook et al [65] Edmond et al [59] Edmond et al [59] Schalet et al [60] Schalet et al [60] Schwartz et al [32] Snellman et al [31] Gerber et al [45] Gerber et al [45] Gerber et al [ [35] Heterogeneity between groups: p = 0.841 Pooled estimate: 10.4% (95% CI: 8.6-12.5) Block et al [94] Block et al [94] Pooled estimate: 10.2% (95% CI: 6.3-16.2) Pooled estimate: 10.5% (95% CI: 7.9-13.9) Lester et al [34] Block et al [94] Watkins et al [37] Milatovic et al [93] Pacifico et al [58] Ginsburg et al [33] Ginsburg et al [89] Watkins et al [37] Block et al [94] Pichichero et al [95] Aronovitz et al [85] Gerber et al [45] Howie et al [54] Aronovitz et al [85] Lennon et al [50] Gerber et al [45] Lennon et al [50] Howie et al [54] Lennon et al [50]…”
Section: Daymentioning
confidence: 99%
See 1 more Smart Citation